The effects of pricing waste generation: A synthetic control approach - Matheus Bueno; Marica Valente (Journal of Environmental Economics and Management, 2019)
To internalize pollution externalities into household waste generation, Unit Pricing Systems (UPS) have been adopted worldwide. This paper evaluates the causal effects of a UPS on the disposal of municipal solid waste in Trento, Italy. Using a unique panel dataset of monthly waste generation in Italian municipalities, we employ the synthetic control method, which allows us to account for possible time-varying effects of unobservables. Our results show that the policy was effective, with a significant decrease of the priced waste stream, unsorted waste, by 37.5%. This effect seems to be largely driven by behavioral changes towards waste avoidance (-8.6%) and possibly by a smaller increase in recycling (+6.1%). By comparing these results to those obtained by a difference-in-differences approach, we show that failing to account for time-varying effects of unobservables may lead to a mismeasurement of policy effects.
Keywords: 330; Waste generation; Unit pricing; Synthetic controls; Policy endogeneity; Selection on unobservables